Measurement of Mobile Banking Application User Satisfaction Using the Technology Acceptance Model (TAM) and Usability Method (Case Study: Bank Kalbar main branch of Pontianak) - Alysha Puji Utami; Nurul Mutiah; Ibnur Rusi (Coding Jurnal Komputer dan Aplikasi, 2022)
This study aims to determine the level of user satisfaction with the Bank Kalbar Mobile application. Bank Kalbar's Mobile is important to measure to determine the level of satisfaction of Mobile Banking application users using the Technology Acceptance Model (TAM) and Usability methods. The Technology Acceptance Model (TAM) method can be a reference in determining various uses and uses of IT from the user's perspective on the benefits and the user's perspective on the use. The TAM method linked to 8 Usability perspectives which consist of learnability, understandability, operability, attractiveness, effectiveness, efficiency, satisfaction, and context of use to design research questionnaires from interrelated indicators. This research questionnaire was distributed to 98 Bank Kalbar‟s Mobile users with the results of measuring user satisfaction with Mobile Banking for the TAM (Perceived Ease of Use) and Usability perspective with an average value of 4.85 very satisfied categories, and TAM (Perceived Usefulness) and Usability perspective with an average value of 4.87 very satisfied category. Then for the results of the Usability calculation, the results of the TAM (Perceived Ease of Use) measurement are 95%, which means it has a very decent value, and the TAM (Perceived Usefulness) measurement results are 96%, which means it has a very decent value. This study also provides recommendations for improvements to the IT Bank Kalbar main branch of Pontianak in optimizing the performance of the Bank Kalbar Mobile application to increase user satisfaction using the action priority matrix.